The Personality of the Main Character in Tiana Amelia's Short Story Menantu Atau Pembantu: Sigmund Freud's Psychoanalysis Study - Nasution, Azhar; Nasution, Mutia (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2024)
Research with the title "The personality of the main character in the short story Menantu Atau Pembantu by Tiana Amelia: Sigmund Freud's Psychoanalysis Study". This study aims to describe the personality of the main character in the short story Menantu Atau Pembantu by Tiana Amelia with story facts as the basis for analysing id, ego, superego in Sigmund Freud's psychoanalysis. The theory used in solving this research problem uses Robert Stanton's story fact theory and Sigmund Freud's personality theory. This type of research uses library research with a descriptive qualitative approach. The data in the research is text in the form of sentence quotations sourced from the short story Menantu Atau Pembantu by Tiana Amelia. The data collection technique uses the reading and note-taking method. The data analysis technique uses the hermeneutic method with analysis steps through data reduction, data presentation and drawing conclusions. The results of this study show that through the facts of the story in the short story, there is a forward plot that describes the personality of the main character with other characters who support the course of the story. The personality of the character described is also motivated by time, place, and socio-cultural background. The results of the analysis of the personality structure according to Sigmund Freud on the main character named Jesi describe the form of id or Jesi's desire is very large, including the desire to have a mother-in-law who is kind and affectionate to her and does not live in one house with her mother-in-law, but the whole id is not all realised by the ego because it can be controlled by the superego. Among the three personality structures, the superego aspect dominates Jesi. Superego is able to postpone the fulfilment of all aspects of id with reality into the achievement of id fulfilment in morality. Keywords: short story of a daughter-in-law or maid, the personality of the main character, Sigmund Freud's psychoanalysis